THE ANOMALOUS STRUCTURE OF KNIPOVICH RIDGE - Gusev E.A.; Shkarubo S.I. (My University, 2001)
The study of bathymetric, single-channel seismic and CDP profiling data, and modern seismicity for the Knipovich Ridge reveals its discordance with respect to the surrounding structural grain, suggesting that it is a recent, superimposed feature. The available geological and geophysical data constrain the inception of the Knipovich Ridge as an oceanic rift to the Miocene. The trend of lineaments, emphasized by the deep structure and present-day seafloor topography on the west flank of the ridge and along its crest, most likely reflects a stress field geometry and a dynamic pattern of tectonic movements dissimilar to the modern structural plan. From the degree of development of structural features of the Knipovich Ridge and from the changes in the mode of its tectonic evolution, which are atypical of mid-oceanic ridges, it is an oceanic rift that is still, structurally, in its formative phase.
Keywords: MID-OCEANIC RIDGE; CDP PROFILING; GEODYNAMICS; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен